Activated carbon production from wastes: profitability index and product cost reduction method (2010)
A previous paper on developing a national capability for the manufacture of activated carbon from agricultural waste by the same authors was considered. In the said paper, the process flow diagram for the manufacture of Granular Activated Carbon from three agricultural wastes namely coconut shell, oil-palm shells and sugarcane bagasse was provided and the plant’s economic analysis done. The objectives of this study were to investigate selling price reducing options and profitability of the investment discussed. In the study, the profitability indexes for the overall plant projects for the three plants were found. The effect of equipment cost reduction on the total productive cost was also examined. For the steam activation of coconut shell, successive reduction by 10% in the overall equipment cost was found reduce the corresponding Product cost geometrically by values ranging from 2.44-1.22% for ten successive reductions. The profitability index was between 0.057 and 4.07% respectively for the 1st to the 11th year. The steam activation of sugarcane bagasse was different, successive reduction by 10% in the overall equipment cost reduce the corresponding Product cost also geometrically by values ranging from 2.85-3.69% (increasing with each reduction) also for 10 successive reductions. The profitability index was between 0.09 and 3.7% respectively for the 1st to the 11th year. And for the phosphoric activation of oil-palm shell, successive reduction by 10% in the overall equipment cost was found reduce the corresponding Product cost geometrically by values ranging from 4.58-2.88% (decreasing with each reduction as in steam activation of coconut shells). The profitability index was between -1.08 and 2.12% respectively for the 1st to the 11th year. In addition, an excel software to simulate the economic analysis previously done and output the key costs after the simulation.